2008
DOI: 10.1118/1.2890085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fixed‐beam IMRT, helical tomotherapy, and IMPT for selected cases

Abstract: A growing number of advanced intensity modulated treatment techniques is becoming available. In this study, the specific strengths and weaknesses of four techniques, static and dynamic multileaf collimator (MLC), conventional linac-based IMRT, helical tomotherapy (HT), and spot-scanning proton therapy (IMPT) are investigated in the framework of biological, EUD-based dose optimization. All techniques were implemented in the same in-house dose optimization tool. Monte Carlo dose computation was used in all cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…In general, the dose to OARs could be substantially lower, in particular to the parotid glands [15][16][17][18][19]21], the larynx [19,21], and the spinal cord [16,19,20]. In one study, no difference was noted among three-, five-and nine-field scanning IMPT [18].…”
Section: Oropharyngeal Hypopharyngeal and Laryngeal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the dose to OARs could be substantially lower, in particular to the parotid glands [15][16][17][18][19]21], the larynx [19,21], and the spinal cord [16,19,20]. In one study, no difference was noted among three-, five-and nine-field scanning IMPT [18].…”
Section: Oropharyngeal Hypopharyngeal and Laryngeal Cancermentioning
confidence: 99%
“…We identified seven studies reporting on ISPC studies among patients with oropharyngeal, hypopharyngeal, and laryngeal carcinoma, including a total of 22 patients [15][16][17][18][19][20][21] (Table 3). In one study, only 3D-CRT using parallelopposed fields was compared with 3D-CPT [15].…”
Section: Oropharyngeal Hypopharyngeal and Laryngeal Cancermentioning
confidence: 99%
“…Although IMPT is able to provide favorable dose distributions [23,30,31,46], the clinical data for IMPT in children with sarcoma are very limited [29]. Timmermann et al [45] reported about IMPT for one case with BP-RMS.…”
Section: Discussionmentioning
confidence: 99%
“…IMRT offers a method of delivering radiation dose conformed to the shape of specific targets while minimizing the dose to the surrounding tissue and nearby critical organs [7,10]. When using the sliding-window technique (Varian Medical Systems, Palo Alto, USA), the MLC leaf pairs sweep over a field during beam-on.…”
Section: Discussionmentioning
confidence: 99%